Exploring low income working mother's perceptions of community support for exclusive breastfeeding after returning to work - Malatjie, Kabelo (Organisational Psychology, 2021)
This qualitative study sought to explore low income working mother's perceptions of community support for exclusive breastfeeding after returning to work. The results from 12 indepth semi-structured interviews conducted with low income mothers, working full-time in a clothing factory located in the Cape Flats area, were analysed using thematic analysis. Three key themes emerged. The mothers generally expressed that they received informational support for breastfeeding from various members of their community, however there was a lack of emotional, instrumental, and appraisal support for these working mothers to continue to exclusively breastfeed after returning to work. Furthermore, the mothers come from communities in which there is a shared responsibility for raising babies. They are often given instructions and advice on how to feed their babies by different people and this advice often contradicts the World Health Organization's breastfeeding recommendations. Lastly, the mothers expressed that breastfeeding is an act that is usually reserved for stay at home mothers. Working mothers' breastfeeding intentions are generally not supported within their communities and working mothers are often encouraged to give their babies formula and other feeds as early as possible. It is important for organisations employing low-income mothers to understand the community context when designing workplace policies and interventions aimed at promoting exclusive breastfeeding. This will allow organizations to address their employees breastfeeding challenges in a culturally sensitive ways.